Morphometric diversity and clustering of wild apricot (Prunus armeniaca L.) in Himachal Pradesh: Implications for phenotypic selection and germplasm management - Anita, K; Dinesh, S; Kehar, ST; Anchal; Sujith, PP (Plant Science Today, 2026)
The present study assesses phenotypic variability, trait correlations and clustering patterns among wild apricot populations across 15 sites of Himachal Pradesh during 2013–2014. Thirteen traits related to tree growth, stone and kernel characteristics were recorded from 75 mature trees (5 trees per site). A wide variation was observed in tree growth and kernel traits, with high genetic gain and heritability for the number of branches and diameter at breast height (DBH). Significant correlations existed among important traits, especially between kernel and stone characteristics. Principal component analysis (PCA) revealed that PC1 accounted for 47.78 % variability, mainly influenced by stone and kernel traits. The PC2 and PC3 contributed 21.07 % and 13.04 %, respectively. Cluster analysis grouped sites into 2 main clusters, distinguishing high-performing sites like Ghar and Panjore, valuable for breeding programs focused on specific trait enhancement and oil content. The study effectively identified significant morphometric diversity and strong trait associations in wild apricot populations. Traits like DBH and branch number emerged as prime selection criteria. The PCA and clustering analysis identified superior, trait-rich sites, supporting targeted breeding, improved oil extraction potential, sustainable conservation and utilisation of wild apricot germplasm.